1981
DOI: 10.1080/15287398109530051
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subchronic toxicity studies of rats exposed to vapors of methyl mercaptan and other reduced‐sulfur compounds

Abstract: Acute inhalation experiments were conducted to determine 24-h LC50 values for adult Sprague-Dawley rats of both sexes exposed to vapors of methyl mercaptan and other reduced-S compounds for 4 h periods. Using calculated gas concentrations, the following LC50 value for each gas and combination was determined: metyhl mercaptan, 675 ppm; dimethyl sulfide, 40,250 ppm; dimethyl disulfide, 805 ppm; hydrogen sulfide, 444 ppm; and an equimolar mixture of methyl mercaptan, dimethyl sulfide, and dimethyl disulfide, 550 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 4 publications
1
27
0
Order By: Relevance
“…They became unable to move around 0.7-1min after exposure. This is similar to previous observations on the acute toxicity and fatality of DMS inhalation as follows: exposure to 4% DMS for 4 h killed 50% of rats within 24 h [8]: a concentration of 5% DMS killed 1 rat in 15 min [9]: a concentration of 9.6% DMS caused 50% rats to be comatose [10]. As the DMS concentration increased, the time until the onset of inability to stand and respiratory arrest became shorter (Table 2).…”
Section: Resultssupporting
confidence: 85%
“…They became unable to move around 0.7-1min after exposure. This is similar to previous observations on the acute toxicity and fatality of DMS inhalation as follows: exposure to 4% DMS for 4 h killed 50% of rats within 24 h [8]: a concentration of 5% DMS killed 1 rat in 15 min [9]: a concentration of 9.6% DMS caused 50% rats to be comatose [10]. As the DMS concentration increased, the time until the onset of inability to stand and respiratory arrest became shorter (Table 2).…”
Section: Resultssupporting
confidence: 85%
“…99 Comparable studies with DMDS revealed an oral LD 50 value for rats of greater than 190 mg/kg, a dermal LD 50 value for rabbits that was greater than 2000 mg/kg, and a 4-hour inhalation LC 50 value for rats of 805 ppm (3.10 mg/L). [100][101][102] A concentration-related increase in olfactory epithelial degeneration was observed in the nasal turbinates of rats exposed to 8.9, 12.6, and 18.4 ppm of DMDS for 24 hours, but a 5.0 ppm exposure for the same duration was free from this effect. 103 A functional observational battery performed on rats exposed to 100, 200, or 700 ppm of DMDS for 6 hours revealed an increased incidence of partial eyelid closure, grooming behavior, and urination, and a decrease in motor and locomotor activity at the highest exposure concentration.…”
Section: International Journal Of Toxicology 33(supplement 1)mentioning
confidence: 99%
“…The conjunctivitis caused by prolonged low-concentration exposure (about 20 ppm) (Lambert et al 2006) is peculiarly associated with reversible chromatic distortion and visual changes. These symptoms are sometimes accompanied by blepharospasm and photophobia (Tansy et al 1981;Milby and Baselt 1999). H 2 S is an odorous gas at low concentration (0.01-0.3 ppm).…”
Section: Neuroinflammation and Other Factorsmentioning
confidence: 99%